Validation of the Recap of Atopic Eczema (RECAP) Measurement Instrument for Eczema Control in Adult Patients in an Asian Clinical Setting - Yik Weng Yew; Crystal Zhen Yu Phuan; Xiahong Zhao; Laura Howells; Christian J. Apfelbacher (Acta Dermato-Venereologica, 2024)
Recap of atopic eczema (RECAP) is a self-reported 7-item questionnaire recommended by the Harmonising Outcome Measures in Eczema initiative to measure eczema control. As RECAP has not been validated in a real-world clinical population in Asia, RECAP was investigated as a measure of eczema control in Singapore. Patients with atopic eczema at the National Skin Centre from July 2019 to January 2020 were included for analysis. Both patient- and physician-reported outcome measures were available for correlation analyses. Correlation analysis was also performed to investigate construct validity, and floor or ceiling effects of RECAP. A total of 260 atopic eczema patients aged between 15 and 87 years were recruited. There were minimal floor and ceiling effects for RECAP scores. There were strong, significant correlations of RECAP with POEM (r = 0.84, p < 0.001) and DLQI (r = 0.81, p < 0.001). Correlation with SCORAD was moderate (r = 0.60, p < 0.001). Correlations remained similar after age, gender, and ethnicity adjustments. Discriminative validity was demonstrated by a significant linear trend of increasing RECAP scores with increasing eczema severity. RECAP demonstrates good discriminative and construct validity evidenced by strong correlations with symptoms and quality of life and moderate correlations with eczema signs. RECAP is useful to measure eczema control in Singapore.